Tectonic expression of an active slab tear from high‐resolution seismic and bathymetric data offshore Sicily (Ionian Sea). Issue 1 (6th January 2016) - Gutscher, Marc‐André; Dominguez, Stephane; de Lepinay, Bernard Mercier; Pinheiro, Luis; Gallais, Flora; Babonneau, Nathalie; Cattaneo, Antonio; Le Faou, Yann; Barreca, Giovanni; Micallef, Aaron; Rovere, Marzia
Abstract: Subduction of a narrow slab of oceanic lithosphere beneath a tightly curved orogenic arc requires the presence of at least one lithospheric scale tear fault. While the Calabrian subduction beneath southern Italy is considered to be the type example of this geodynamic setting, the geometry, kinematics and surface expression of the associated lateral, slab tear fault offshore eastern Sicily remain controversial. Results from a new marine geophysical survey conducted in the Ionian Sea, using high‐resolution bathymetry and seismic profiling reveal active faulting at the seafloor within a 140 km long, two‐branched fault system near Alfeo Seamount. The previously unidentified 60 km long NW trending North Alfeo Fault system shows primarily strike‐slip kinematics as indicated by the morphology and steep‐dipping transpressional and transtensional faults. Available earthquake focal mechanisms indicate dextral strike‐slip motion along this fault segment. The 80 km long SSE trending South Alfeo fault system is expressed by one or two steeply dipping normal faults, bounding the western side of a 500+ m thick, 5 km wide, elongate, syntectonic Plio‐Quaternary sedimentary basin. Both branches of the fault system are mechanically capable of generating magnitude 6–7 earthquakes like those that struck eastern Sicily in 1169, 1542, and 1693. Key Points: First clear observations of surface tectonics of a slab tear High‐resolution bathymetric and seismic images of unprecedented quality Two active fault systems at the seafloor (60 and 80 km long) may pose seismic hazard